Predicting Financial Survival: Altman Z-Score Insights into India's Renewable Energy Industry. - Md Sohail PERWEZ; Ruksar AHMAD (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study evaluates the financial health and bankruptcy risk of seven major Indian renewable energy firms from 2014 to 2023 using the Altman Z-score model, specifically its version adapted for emerging markets. As India targets 450 GW of renewable energy capacity by 2030, understanding the financial resilience of key industry players is essential to guide investment strategies and policy decisions. The selected firms, Tata Power Renewable Energy, Adani Green Energy, Suzlon Energy, Inox Wind, NHPC, SJVN, and Reliance Power, represent a mix of ownership structures and operate across solar, wind, and hydro sectors. A quantitative approach was applied using publicly available financial data, incorporating key ratios such as working capital, retained earnings, EBIT, and market value of equity. The results reveal variation in financial performance: Adani Green consistently remained in the green zone after 2020, reflecting strong investor confidence and low insolvency risk, while NHPC and Reliance Power stayed in the distress zone throughout, suggesting persistent financial weakness. Suzlon Energy showed volatility but signs of recovery by 2023, whereas Inox Wind moved from stability to distress after 2017. These findings support the use of the Z-score as a financial early-warning tool in capital-intensive sectors. However, the model’s limitations are evident in its inability to fully capture industry-specific challenges like delayed subsidies, regulatory uncertainty, and long asset payback periods. The study recommends integrating financial ratios with sector-specific and qualitative indicators.It contributes to the literature by applying the Z-score in India’s renewable energy context and offers practical insights for investors and policymakers.